2015
DOI: 10.1007/s00421-015-3202-0
|View full text |Cite
|
Sign up to set email alerts
|

Timing of post-exercise carbohydrate ingestion: influence on IL-6 and hepcidin responses

Abstract: The timing and ingestion of post-exercise carbohydrate ingestion do not appear to impact post-exercise interleukin-6 and hepcidin responses; this is likely a result of the interval running task inducing an inflammatory response and subsequent up-regulation of hepcidin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 44 publications
6
33
0
Order By: Relevance
“…In addition, the timing of carbohydrate supplementation appears to be a factor in plasma IL‐6 levels. Studies that solely provided subjects with carbohydrate before (63) or after (64, 65) exercise failed to observe an attenuation in plasma IL‐6 concentrations, suggesting that carbohydrate must be consumed during exercise to observe an attenuation in circulating concentrations of muscle‐derived IL‐6. Moreover, studies involving eccentric exercise failed to observe an attenuation in the increase in circulating concentrations of muscle‐ (61) or immune cell–derived (64) IL‐6.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the timing of carbohydrate supplementation appears to be a factor in plasma IL‐6 levels. Studies that solely provided subjects with carbohydrate before (63) or after (64, 65) exercise failed to observe an attenuation in plasma IL‐6 concentrations, suggesting that carbohydrate must be consumed during exercise to observe an attenuation in circulating concentrations of muscle‐derived IL‐6. Moreover, studies involving eccentric exercise failed to observe an attenuation in the increase in circulating concentrations of muscle‐ (61) or immune cell–derived (64) IL‐6.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
“…, subjects were in the postabsorptive state) and consume a carbohydrate beverage or a noncaloric placebo beverage ( e.g. , artificially sweetened water with electrolytes) (10, 4756, 5865) during prolonged exercise lasting >2 h. Studies that provided subjects with a standardized breakfast <2 h before exercise (56, 58, 59) ( i.e. , subjects were in the fed state) and that had subjects consume a placebo or carbohydrate beverage during exercise lasting <2 h failed to demonstrate attenuation in plasma IL‐6 levels after exercise.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recovery periods encompassed 90 s of active-recovery at 5 km·h -1 . This particular interval running protocol was adapted from previous research conducted in our laboratory, which has shown a significant haemolytic responses to the type of work completed here (Badenhorst et al, 2015;Badenhorst et al, 2014;Sim et al, 2013). Furthermore, interval running training has been shown to result in a greater haemolytic response as compared to a distance matched, low intensity continuous run (Peeling et al, 2009).…”
Section: Experimental Overviewmentioning
confidence: 99%
“…Sufficient evidence has revealed that various types of exercise increase the serum hepcidin level during the postexercise period (Badenhorst et al., 2015a; Domínguez et al., 2018; Goto, Kasai, Kojima, & Ishibashi, 2018; Goto, Sumi, Kojima, & Ishibashi, 2017; Peeling et al., 2017). Moreover, the increase in postexercise hepcidin level has been attributed to exercise‐induced increases in interleukin (IL)‐6 in iron sufficient individuals (Badenhorst et al., 2015a, 2015b; Peeling, 2010). As a support of this idea, lipopolysaccharide (i.e., a protagonist of the inflammatory response) injection increased IL‐6 levels with subsequent elevation of urinary hepcidin levels peaked 3 hr thereafter (Kemna, Pickkers, Nemeth, van der Hoeven, & Swinkels, 2005).…”
Section: Introductionmentioning
confidence: 99%